Metoda Sederhana Distribusi Node Jaringan Sensor Nirkabel untuk Mengatasi Kehilangan Data Pada Saat Pengiriman - Rifki Muhendra (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
A simple method of wireless sensor network node distribution was developed to address data loss during transmission. A node consists of a microcontroller, radio frequency, and battery. The adjacent nodes are planted with programs that can build mesh networks. This network consists of multiple child networks and parent networks connected through a frequency router node. Communication between nodes in the network can take two ways. The average ping time measured for the node distribution model is small from 1 second and the bit error rate (BER) is 0%. Index Terms—Wireless sensor networks, mesh, frequency router node